The rhetoric of judging well : the conflicted legacy of Justice Anthony M. Kennedy - Frank, David A.; Mootz, Francis J., III (Rhetoric and democratic deliberation, 2023)
"A collection of essays providing an interdisciplinary account of U.S. Supreme Court Justice Anthony M. Kennedy's judicial rhetoric"--